Magnetic Circuit Design and Magnetic Field Finite Element Analysis of Converging Stepped Magnetofluid Seal with Small Clearance - Xiaolong Yang; Guohong Wang; Ruibo Zhang (Advances in Materials Science and Engineering)
The stepped magnetofluid seal is an effective method for improving the pressure ability of ordinary magnetofluid seals (OMS) with large clearance. At present, the research on stepped magnetofluid seal with less than 0.4 mm small clearance has not been carried out yet. The equivalent magnetic circuit design of converging stepped magnetofluid seal (CSMS) with small clearance has been carried out and verified by magnetic field finite element method based on the CSMS theory and magnetic circuit theory. The effects of the width of the axial seal position, the height of the radial seal position, the number of the pole tooth in the axial seal position, and the number of the pole tooth in the radial seal position on the theoretical pressure ability of the CSMS are investigated by numerical simulation. The calculation results are analyzed and discussed. The results show that the magnetic flux leakage at the junction of the permanent magnet and pole piece causes the higher pressure ability of the CSMS structure designed by the equivalent magnetic circuit method than that calculated by the magnetic field finite element method. When the width of the axial seal position is greater than the height of the radial seal position and the number of pole teeth in the axial seal position is less than the number of pole teeth in the radial seal position, the CSMS has the best effect. Compared with OMS with small clearance, CSMS has greater advantages.